HUBUNGAN KARAKTERISTIK SOSIAL EKONOMI DAN SISTEM SUMBERDAYA DENGAN KELEMBAGAAN MASYARAKAT PADA DAERAH PENYANGGA TAMAN NASIONAL GUNUNG HALIMUN SALAK (Studi Kasus di Kabupaten Bogor, Lebak dan Sukabumi) - Windra Kurniawan; Cecep Kusmana; Sambas Basuni; Aris Munandar (Jurnal Penyuluhan Pertanian, 2020)
Boundary area management is affected by four factors which are natural resources,human resources technology and institutions. The aimed of this research was to analyze therelationship between social economic dan the resource systems with community institutionson boundary area of Halimun Salak Mountain National Park. The result showed that averageof respondents’ age was 44 years with education level was elementary school and junior highschool, income acerage was Rp 172,758.60/capita/month. The ownership of respondents housewas self owner. Mostly the ownership land status of samples was renting with narrow landauthorities. Income average of group members was Rp 412,500.00. The level of accessibilityand management’s rule locally was 76.43%. Meanwhile, the simplicity in implementing ruleslevel was 68.98%. Gradual sanction level was 67.75%. The accountability level of themonitoring staff was 64.97%. Whereas, the level of relationship between resource system andinstitutions management was 63.85%. The level collective commitment to formulate rules was82.11%. The level of adjusting toward the rules gradually to all members was 62.78%. Thelevel of solving disagreement method was 59.22%. The level of controlling capability for theresource purpose was 60.11%. The level of relationship between resource system andinstitutions management was 58.50%. The level of low cost technology appropriateness was36.05%. The time adaptation toward new technology was 1.91 months. The government fundassisting for institutions/groups was Rp 14.533.333,33. Perception on institution had positivecorrelation with education level and distance from their living area.